Community Enhancement Through Participatory Planning: A Case Of Tsunami-Disaster Recovery Of Banda Aceh City, Indonesia - Harahap, Grace Yuswita (2013)
This research aims to understand the mechanisms and procedures of public participation process in tsunami-affected areas and to examine whether or not the process contributed to the recovery of affected-community. The evaluation of public participation has been well documented; however, the evaluation framework is deficient in assessing the extent to which participation process has been successful in the fulfilment of its purpose—within the bigger context of development which it belonged. In post-disaster context, redevelopment programs are strongly expected to play a role in recovery of community. In conducting this ex-post evaluation study, mixed methods approach is utilized, i.e. survey and personal interview. Survey data is analyzed descriptively and interview data thematically. Both analyses are combined to enhance understanding on participation matters. The instrument is developed by using Rowe and Frewer’s evaluation framework criteria—to evaluate participation process, and additional self-developed criteria—to evaluate the recovery of affected-community. By involving 44 respondents in survey and 33 of them in interview in four most devastated villages in Banda Aceh, the results show that (i) participation was accepted as a major effort to accommodate community views and considered competent in involving affected-community in the participation process; and (ii) community’s sense of confidence was restored during/after the participation process and they became optimistic about their life. It is evident that the manner in which participation was facilitated was fundamental for participation process to fulfil its purpose. Hence, the study contributes to the broadening of the context, and deepening the scrutiny, of the existing evaluation approach on public participation process. Further research is expected to develop a more comprehensive and compact evaluation framework to evaluate the restoration of socio-economic vitality of affectedcommunity, in an effort to ascertain whether or not the community is making progress towards becoming a disaster resilient community—as the primary goal of disaster recovery efforts.